The Modes of Appropriation. Foucault and Bakhtin on the Aesthetization of Life - Koczanowicz, Leszek (Problemos, 2003)
The idea of aesthetic existence appeared in 19th century. It was popular among avant-gard elites as a Challenge to bourgeois world. It was also developed in a more philosophícal way in Lebensphilosophie and existentialism. In this paper two different 20th century approaches to the notion of aesthetic are discussed: conceptions of Michael Foucault and Mikhail Bakhtin. Both of them closely link the notion of aesthetic with the idea of the self. Although Foucault makes the concept of aesthetic existence central to his later works in philosophícal anthropology, while Bakhtin fully rejects its usefulness for the constitution of the self, both discuss it extensively as an important point of departure for the understanding of the self.
Keywords: aesthetic existence; the self; the other; ethics